IMPLEMENTATION OF THE SEVERANCE PAYMENT AGREEMENT FOR EMPLOYEES OF PT. GADING BHAKTI : (Case Study of PT. Gading Bhakti in the Pantoen Reu District, West Aceh Regency) - Eka Aria Mawar; Dara Quthni Effida (Transpublika Publisher, 2023)
PT. Gading Bhakti, a private company and subsidiary of PT. Mapoli Raya, operates in the palm oil plantation and processing industry. In 2021, PT. Mopli Raya, its parent company, was declared bankrupt under Decree Number 17/pdt-SUS-PKPU/2020/PN.Niaga Medan and Law No. 13 of 2003, Employment Article 95 paragraph 4, mandating debt settlement as a priority for bankrupt companies. Despite this, PT. Gading Bhakti failed to fulfill debt payments to 25 retired employees, resulting in the non-payment of their post-employment benefits. The research aims to investigate the implementation of the severance payment agreement by PT. Gading Bhakti and the company's measures to meet its obligations toward employee severance. The research methodology employed was the empirical juridical method, observing ongoing events and directly examining PT. Gading Bhakti's implementation of the severance payment agreement. Furthermore, the study explores the company's attempts to fulfill the severance payment for its employees. Regrettably, the implementation of the agreement resulted in a breach of contract, with severance payments not being duly honored. Various efforts were made, including rescheduling the agreement and submitting severance payment documents. On the other hand, the employees sought resolution through verbal warnings, mediation, media involvement, and seeking assistance from relevant authorities concerning the unclear situation of severance payments for PT. Mapoli Raya's ex-employees (PT. Gading Bhakti being its subsidiary). In conclusion, the study highlights the challenges faced by retired employees in receiving their post-employment benefits and the need for PT. Gading Bhakti to effectively fulfill its obligations regarding severance payments.